A COMPARATIVE STUDY OF MARKETING MIX AND RETAIL SERVICE QUALITY SCALE (RSQS) ON MINIMARKET (CASE STUDY: INDOMARET AND ALFAMART TATAARAN 2) - Wuisang, Virginia Michelle; Pangemanan, Sifrid S.; Rumokoy, Farlane S. (Jurnal EMBA: Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2019)
Abstract: Changes in lifestyle that demand easiness in meeting the needs and wants of every individuals are one of the reason for the development of retail business in Indonesia. There are two major retailers, which is Indomaret and Alfamart, both competing in their marketing mix and retail service quality scale. The purpose of this research is to compares the marketing mix and retail service quality scale indicators between Indomaret and Alfamart. The population is the customers of Indomaret and Alfamart in Tataaran 2 with the sample of 100 respondents and analyzed using the Independent Sample T-Test analysis. The result shows that there are no significant difference in terms of the marketingÂ  mix. Meanwhile, it shows that there are difference in terms of the retail service quality scale based on the physical aspect and policy.Â Keywords: retail corporate image, alfamart, indomaret